Biomarkers for early detection and predicting outcomes in acute kidney injury. (2nd August 2022) - Cottam, Daniel; Azzopardi, Giada; Forni, Lui G
Abstract : The current diagnosis of acute kidney injury relies on the measurement of serum creatinine levels and urine output. However, both measures are subject to considerable limitations; for example, change in serum creatinine levels ideally requires a knowledge of baseline function that is often not available. Furthermore, creatinine levels are influenced by many factors including diet, drug therapy, muscle mass, gender and ethnicity, which may lead to underestimation of the extent of renal dysfunction. Similarly, urine output lacks both specificity and sensitivity as a marker of acute kidney injury given that oliguria may be an appropriate physiological response to a multitude of stressors and that output may be maintained until significant renal damage has already occurred. Given the well-documented consequences of acute kidney injury and the considerable burden associated with its development, much attention has focused on early identification of patients at high risk to try and improve outcomes. Many studies have focused on the identification of candidate molecules that may enable the early detection of individuals at risk of developing acute kidney injury, including constitutive proteins associated with kidney damage, as well as molecules upregulated in response to injury, non-renal products that may be filtered, reabsorbed or secreted by the kidney, and markers of renal stress. Such biomarkers may also aid stratification for adverse events, such as the need for kidney replacement therapy or progression to chronic kidney disease and end-stage kidney disease. This article discusses some of these novel biomarkers and assesses the role they may have in the understanding, management, diagnosis and prognostication of acute kidney injury.